Factors associated with married women's support of male circumcision for HIV prevention in Uganda: a population based cross-sectional study - Komi Mati; Korede K. Adegoke; Hamisu M. Salihu (BMC, 2016)
Abstract Background Despite the protective effect of male circumcision (MC) against HIV in men, the acceptance of voluntary MC in priority countries for MC scale-up such as Uganda remains limited. This study examined the role of women's sociodemographic characteristics, knowledge of HIV and sexual bargaining power as determinants of women's support of male circumcision (MC). Methods Data from the Uganda AIDS Indicator Survey, 2011 were analyzed (n = 4,874). Bivariate and multivariate logistic regression analyses with random intercept were conducted to identify factors that influence women's support of MC. Results Overall, 67.0 % (n = 3,276) of the women in our sample were in support of MC but only 28.0 % had circumcised partners. Women who had the knowledge that circumcision reduces HIV risk were about 6 times as likely to support MC than women who lacked that knowledge [AOR (adjusted odds ratio) = 5.85, 95 % CI (confidence interval) = 4.83-7.10]. The two indicators of women's sexual bargaining power (i.e., ability to negotiate condom use and ability to refuse sex) were also positively associated with support of MC. Several sociodemographic factors particularly wealth index were also positively associated with women's support of MC. Conclusions The findings in this study will potentially inform intervention strategies to enhance uptake of male circumcision as a strategy to reduce HIV transmission in Uganda.